Seasonal variation in food habits of the Italian hare in a south Apennine semi-natural landscape. Issue 2 (2nd April 2016) - Freschi, P.; Fascetti, S.; Musto, M.; Cosentino, C.; Paolino, R.; Valentini, V.
Abstract : The Italian hare is a species of hare endemic to central and southern Italy and to Sicily. It has been classified as a 'vulnerable' species by the International Union for Conservation of Nature (IUCN), as it is considered to have a high risk of extinction in the next decade. Despite its endangered status, little is known about its feeding habits. In the present study, the seasonal pattern of diet composition of a population of Italian hare occupying a semi-natural landscape was estimated by using the micro-histological technique of faecal analysis. The results showed that hares had a diversified diet, consuming plant parts from over 70 species. Like other Lepus sp., the Italian hare consumed a large amount of herbaceous plants (e.g. Brachypodium sylvaticum, Trifolium pratense, Allium subhirsutum and Festuca arundinacea ), although it complemented its diet seasonally with fruits of Prunus spinosa, Pyrus piraster and Malus sylvestris . Analysis of similarities (ANOSIM) evidenced significant differences among seasons, as a consequence of the seasonal occurrence of the various food items. Spring and autumn ( R = 0.7482, P = 0.001), as well as spring and winter ( R = 0.7398, P = 0.001), showed low diet similarities; these results were supported by similarity percentage analysis (SIMPER, average dissimilarity: > 71% between spring and autumn; > 69% between spring and winter) with taxa like P. spinosa, Cirsium strictus, T. pratense and Rosa canina making the greatest contributions to these differences. Higher similarities were instead found when comparing other seasons. This seasonal pattern of diet composition was clearly depicted in the graph from nonmetric multidimensional scaling (n-MDS) ordination. Our results highlight the importance of some plant taxa in the diet of the Italian hare and could be useful in managing reintroduction programs.